2006
DOI: 10.1515/cclm.2006.138
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of homocysteinemia in patients with congestive heart failure

Abstract: Elevated homocysteine levels observed in CHF patients, whatever the etiology of their heart disease (ischemic or non-ischemic), were correlated with the severity of the disease. Hyperhomocysteinemia appears to be a predictive factor of mortality in CHF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
(23 reference statements)
2
15
0
1
Order By: Relevance
“…Some studies have proposed a mechanism whereby a high homocysteine level could cause heart failure. Additionally, some studies have reported that vitamin supplementation, including folic acid supplementation, improved the potency of vasodilation and decreased blood pressure, 32,33) whereas others have suggested that such supplements are not effective. 6,34,35) Therefore, in addition to evaluating the long-term outcome of the subjects in this study, further studies on the possible benefits of vitamin supplementation are necessary.…”
Section: Limitationsmentioning
confidence: 99%
“…Some studies have proposed a mechanism whereby a high homocysteine level could cause heart failure. Additionally, some studies have reported that vitamin supplementation, including folic acid supplementation, improved the potency of vasodilation and decreased blood pressure, 32,33) whereas others have suggested that such supplements are not effective. 6,34,35) Therefore, in addition to evaluating the long-term outcome of the subjects in this study, further studies on the possible benefits of vitamin supplementation are necessary.…”
Section: Limitationsmentioning
confidence: 99%
“…Since HL-1 cells are known to demonstrate the same phenotype as primary culture cardiomyocytes, we did not view this as a limitation. The duration of time for treatment in vitro (24 hours) was chosen since it is known that treatment of cells with receptor agonists for many minutes or hours resulted in a loss of cellular receptors (downregulation) 6. If downregulation is going to occur, it is likely to be captured within this period of time.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that treatment of cells with receptor agonists for many minutes or hours results in a loss of cellular receptors (downregulation) 6. Hence, this treatment would have been sufficient to evoke receptor downregulation and variable G protein content if Hcy is, indeed, an agonist to GPCRs utilizing these G proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HHcy is associated with faster progression of coronary plaque (16) and higher probability for recurrent cardiovascular events (6,9). In myocardial infarction, HHcy is considered a predictive factor of mortality, independent of other predictive factors (4,17,18).…”
Section: Discussionmentioning
confidence: 99%